Tawatu Dalam Kajian Fiqih Dan Konsekuensinya Pada Transaksi Keuangan (Muamalah Maliyah) - Muhammad Riza Aziziy; Mahmudah Mahmudah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2018)
In the fiqih muamalah studies agreement between the parties who transact is very important in determining the validity of the transaction (luzum). And agreement or willingness in the transaction is also very decisive to the halal or not the acquired property. Basically, muamalah law can be done, unless there is a proposition that forbid it. This rule implies the extent of muamalah issues faced by the ummah, thus demanding to continue to perform creative and innovative economic contracts. With the principle of ridlo and mubah above, and the opening possibility to innovate in commercial contracts, not infrequently people do engineering (hilah) against a contract. Not a few hilah that preclude a contract to be haram, instead of transforming from the unattractive to be creative and mubah. Agreements made by the parties who transact to do engineering on the contract that is called tawatu 'or muwato'ah.